Gebėjimai socialinio darbo praktikoje (tėvystės ir vaikų socialinių gebėjimų lavinimas) Practical skills of social work - Vyšniauskytė-Rimkienė, Jorūnė (Vytautas Magnus University, 2012)
The textbook provides an overview of interview method in social work, presents theoretical background and practical methods for social skills training for children and youth, aquitance with the importance and pecullarities of parenting competence at different age periods of children, parenting skills methods and models. Social work students, practitioners and others profesionals can find useful material for planning and organizing interview with different groups of clients, can gain practical recommendations how to organize children social skills and parenting skills trainings.